Fashion Industry in the Context of Sustainable Development: Eco-Products, Conscious Consumption and Management - Олександра Кулакова; Олена Костюченко; Олена Тимошенко (Socio-Cultural Management Journal, 2021)
Introduction. The relevance of the study is due to the need to select management tools for the formation of environmentally conscious consumption of the fashion industry products, which is developing dynamically and rapidly, which will contribute to the preservation of the resource potential of not only the country but also the planet as a whole. Purpose and methods. The purpose of the article is to substantiate the role and importance of eco-products, conscious consumption, and management in the context of the fashion industry’s sustainable development. The methodological basis of the study is an interdisciplinary approach to the consideration of the problem of managing the conscious consumption of eco-fashion products when its economic, environmental, technical, organizational, social, psychological, and physiological functions are realized in the relationship. Results. Perspective trends in the fashion industry development from the point of view of conscious rational and ecological consumption of clothing have been identified. The role of a socially responsible attitude to clothing production, which affects the ecology of the environment, is substantiated. The theoretical bases of sustainable development and progress of the Ukrainian fashion industry on the example of formation and promotion of Ukrainian designers’ fashion brands are considered. Conclusions. As a result of the conducted study, the main motives for creating eco-products in the fashion industry, as well as the main environmental concepts, are outlined. The importance of choosing optimal tools and management strategies aimed at greening the production of eco-products was determined by the fashion industry enterprises. The scientific novelty of the study consists in the interdisciplinary deepening of the theoretical provisions of production management and conscious consumption of the fashion industry eco-products in the conditions of greening the public space.